The Role of Counselors in the Development of Career Planning for Youth Inmates - Afdal, Afdal; Elviana, Elviana; Alizamar, Alizamar (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2017)
Adolescence is a period of transition from childhood to adulthood. During the course of developmental tasks, teenagers often fall into the negative direction that causes them to commit acts that violate the law so that sanctions in the form of criminal punishment. One of the developmental tasks traversed by teenagers is the task of selecting and planning future jobs/careers. However, the conditions faced by teenagers inside the Prison are very complicated. Lack of information about careers that can be inmates in their teens, this makes it difficult for them to make career planning in the future. This paper discusses the role of counselor in helping career planning for inmates in their teens.